The covenant (Abram's daughters, 1, 2002)
Years of secrecy bind the tiny community of Gobbler's Knob together more than the present inhabitants know, and the Plain folk who farm the land rarely interact with the fancy locals. So when Sadie is beguiled by a dark-haired English boy, it is Sadie's younger sister, Leah, who suffers from her sister's shameful loss of innocence. And what of Leah's sweetheart, Jonas Mast, sent to Ohio under the Bishop's command? Drawn into an incomprehensible pact with her older sister, Leah finds her dreams spinning out of control, even as she clings desperately to the promises of God. The Covenant begins a powerful Lancaster portrait of the power of family and the miracle of hope.

The Preacher's Daughter (Annie's people, 1,, 2006)
"Annie Zook--the preacher's eldest daughter--is expected to join the Amish church, but at 20 she is 'still deciding.' Because of the strict rules that guide the Plain community, she must continually squelch her artistic passion, although it has become her solace"--Provided by publisher.

The brethren (Annie's people, 3,, 2006)
Torn between her forbidden art and the Amish church, Annie Zook, the preacher's daughter, moves from her childhood home to live with her shunned friend, Esther, which increases her community's disapproval of her.